(untitled) (Panacea Journal of Medical Sciences, 2025)
Introduction: The global escalation in social media engagement, particularly among adolescents and young adults, has elicited significant concern regarding its impact on psychological well-being. Empirical studies have identified a correlation between excessive social media usage and heightened incidences of mental health issues, including depression, anxiety, and psychological distress. Notably, research indicates that adolescents engaging with social media platforms for more than three hours daily exhibit a higher propensity for experiencing mental health challenges. Moreover, the pervasive use of social media has been associated with disturbances in sleep patterns, further exacerbating psychological distress. These findings underscore the necessity for moderated and mindful social media consumption to mitigate potential adverse effects on mental health. Aim & Objectives: The study aims to evaluate the usage of social networks and their impact on anxiety and depression among undergraduate students in medical, dental, and nursing professions. The specific objectives include estimating the extent of social network usage among these students and assessing the levels of anxiety and depression associated with social networking use. Materials and Methods: This study aimed to assess social networking usage, its influence on anxiety & depression among undergraduates. 620 undergraduates were included in the study. Social networking usage questionnaire, The Depression, Anxiety & Stress Scale-21 items(DASS-21 scale) along with semi-structured proforma was used to collect the data. Statistical analysis was done using SPSS version 25 and appropriate statistical tests were performed. Results: Mean age was 20.14±1.281. Social Networking Usage Questionnaire (SNUQ)-academic scores were higher in 70% of the participants. Majority had higher Social Networking Usage Questionnaire (SNUQ)-socialisation scores. Majority had higher Social Networking Usage Questionnaire ( SNUQ)-entertainment scores. Social Networking Usage Questionnaire (SNUQ)-informativeness scores were higher in 57.9% subjects. Mean of SNUQ scores is 55.48± 9.04 indicating moderate level of usage. According to DASS-21 scale, 85.6% had depression. 98.4% were having anxiety. Pearson correlation of SNUQ-academic score and DASS-anxiety score, SNUQ-entertainment score and DASS-depression score was positive which was statistically significant. Conclusion: This study demonstrates increase in social media usage among students both for academic and non-academic purposes. Social media usage was associated with negative mental health outcomes such as anxiety and depression.